Formation of critical thinking in junior schoolchildren through problem-based tasks. - Byhar, Н; Shevchuk, K; Shestobuz, О; Hordiichuk, О; Pits, І (My University, 2024)
The development of critical thinking is an essential component of modern education. This study aimed to identify the impact of problem-based tasks on developing critical thinking in primary school students. The research methods included Watson-Glaser testing, Cornell Critical Thinking Test (level X), ANOVA and correlation analysis. The results showed a significant improvement in the experimental group: in the category “Identifying Facts”, the average score increased from 3.5 to 5.5, in “Interpreting Data” - from 4.0 to 6.0, and in “Drawing Conclusions” - from 3.0 to 5.0. Also, in the “Situation Analysis” category, the score increased from 3.2 to 5.3, and in “Hypothesis Formulation”, from 2.8 to 4.7. The final score of the experimental group increased from 12.3 to 16.5, while the control group showed only a slight improvement (from 11.8 to 12.0), confirming the effectiveness of problem-based tasks. The practical significance of the results in introducing problem-based tasks to develop students' critical skills makes the study's findings applicable and valuable. Prospects for further research include the study of long-term effects and the impact of socio-economic factors on the effectiveness of these methods.
Keywords: analysis, cognitive skills, critical thinking, educational process, primary school students, problem-based tasks, reflection.